A study on the need and impact of emotional intelligence with special reference to managerial effectiveness in the organization - Vani Murugesan, Mrs.; H Sankaran, Dr (International Journal of Engineering and Technology, 2018)
Emotional intelligence (EI) plays avital role in enhancing managerial effectiveness, which is closely related to the professional growth and achievement of an individual in any organization. The study intends to discover the impact of various attributes of EI on the managerial effectiveness in inorganization. Various researches in the past haved hailed Emotional Intelligence as critical to succeed in professional roles. Four factors (i.e.) Self-management, Self-regulation, Internal motivation and empathy had been taken into study to measure the managerial effectiveness of employees [1]. The methodology concerned with this system uses responses based on certain variables, which are closely related to emotional intelligence and managerial effectiveness in an organization. Results show that these four factors have a positive implication on the managerial effectiveness and on the professional performance of an manager in organization